Peningkatan Kompetensi Pengoperasian PLC Siswa Program Keahlian TITL Kelas XI SMKN 2 Karang Baru melalui Penggunaan Model Pembelajaran Berbasis Masalah - Rina Gusti Nasution (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
The aims of this research are: (1) to find out how much the improvement in PLC operating competence of students in the TITL skill program at SMKN 2 Karang Baru through the use of a problem-based learning model with the help of the Zelio SR2B201BD PLC trainer learning media with traffic light applications seen from the learning outcomes of the affective domain; (2) to find out how much the improvement in PLC operating competence of the TIPTL skill program students of SMKN 2 Karang Baru through the use of problem-based learning models assisted by learning media for PLC trainer Zelio SR2B201BD with traffic light applications seen from the learning outcomes of the cognitive domain; (3) to find out how much the improvement in PLC operating competence of students in the TITL skill program at SMKN 2 Karang Baru through the use of a problem-based learning model assisted by learning media for the PLC trainer Zelio SR2B201BD with traffic light applications seen from the learning outcomes of the psychomotor domain. This research is a Classroom Action Research (CAR). The subjects of this study were students of class XII CI-BI Electrical Power Installation Engineering Expertise Program (TITL) SMKN 2 Karang Baru, totaling 26 people. The improvement of competence to be achieved is viewed from the three domains of student competence, namely; affective aspects, cognitive aspects and psychomotor aspects. The data on the students' affective and psychomotor aspects were collected using the observation sheet instrument for affective and psychomotor observations. Data on students' cognitive aspects were collected using a test instrument, which was given at the end of each cycle. The results of the research in the first cycle of student competence were still low, while in the second cycle it increased and reached the established indicators of success. The improvements are: 1) for the affective domain of 4.4, from 14.1 in the first cycle to 18.5 in the second cycle with a maximum score of 20 and getting a very good category, 2) for the cognitive domain of 8.64, from 75 .77 in the first cycle to 84.42 in the second cycle, 3) for the psychomotor domain of 25.68, from 57.63 in the first cycle to 83.31 in the second cycle.